2018
DOI: 10.1093/ntr/nty261
|View full text |Cite
|
Sign up to set email alerts
|

A Procedure to Standardize Puff Topography During Evaluations of Acute Tobacco or Electronic Cigarette Exposure

Abstract: Introduction Documenting factors that influence differential sensitivity to acutely inhaled nicotine products requires carefully controlling the amount of exposure (dose), and thus a procedure by which to control such exposure. Methods We evaluated consistency of puff volume from intermittent acute exposures to smoked tobacco cigarettes (study 1, n = 45, plus a comparison study of uninstructed use with n = 59) and to vaped el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…32 To ensure the same controlled smoke exposure from each cigarette, timing and duration of each puff was controlled by computer-displayed instructions. 33 This pattern of exposure allowed intervals of 15 minutes between trials while minimizing smoking satiation or toxicity. Total exposure over each 2-1/2 hour discrimination testing procedure was 40 puffs, or about four full cigarettes, under deprived conditions after overnight abstinence, with 20 puffs from the ultra-low and 20 from the other Spectrum cigarettes, nearly all of which were lower in nicotine than commercial brands.…”
Section: Methodsmentioning
confidence: 99%
“…32 To ensure the same controlled smoke exposure from each cigarette, timing and duration of each puff was controlled by computer-displayed instructions. 33 This pattern of exposure allowed intervals of 15 minutes between trials while minimizing smoking satiation or toxicity. Total exposure over each 2-1/2 hour discrimination testing procedure was 40 puffs, or about four full cigarettes, under deprived conditions after overnight abstinence, with 20 puffs from the ultra-low and 20 from the other Spectrum cigarettes, nearly all of which were lower in nicotine than commercial brands.…”
Section: Methodsmentioning
confidence: 99%
“…Although most participants in this study were naïve to e-cigs, the degree of liking and/or familiarity with the e-cigs that we prepared would be a confounding factor. In this context, previous research demonstrated that the e-cigs flavor has impacted to reduce cigarette use and quit smoking (Yang et al, 2020); the flavor to e-cigs was highly associated with nicotine consumption (Patten et al, 2021); and the administration of puff inhalation, breath-hold, and exhalation may increase control over amounts of acute exposure to cigarette use (Perkins and Karelitz, 2020). However, Perkins and Karelitz reported that the number of puffs and the duration of puff were different between instructed and uninstructed procedures (Perkins and Karelitz, 2020); it is possible that the smoking craving may not be completely satiated.…”
Section: Discussionmentioning
confidence: 99%
“…We further controlled nicotine dosing with Spectrum by using our validated and reliable puffing procedure, which instructs participants on precisely when and for how long to take each puff to target intake at 60 ml per puff (typical of that during ad lib puffing). That procedure carefully standardizes intake from smoking, as well as from vaping e-cigarettes (Perkins & Karelitz, 2020b).…”
Section: Spectrum Low and Very Low Nicotine Research Cigarettesmentioning
confidence: 99%